Development of a Biocompatible Hydrogel Platform for Wound Healing and Skin Regeneration - Ibrahim, Ranya (University of the Witwatersrand, Johannesburg, 2024)
The skin wound healing process is a meticulously coordinated event involving the reconstruction of various cell types within the epidermal and dermal layers. In severe conditions like severe cutaneous wounds, the normal wound healing process is either delayed or fails to restore the injured tissue's normal structure and function adequately, leading to skin ulceration or other alterations. This has prompted the exploration of advanced therapeutic options such as gene therapy, growth factor therapy, platelet-rich plasma (PRP) therapy, stem cell-based therapy, and tissue engineering. Stem cell-based therapy has recently gained attention for its potential in treating cutaneous wounds due to the therapeutic capabilities of these cells. Despite encouraging results, certain limitations need consideration. A significant challenge in stem cell-based replacement therapy is the low survival rate post- transplantation. Additionally, tumour-initiating cells share many characteristics with normal stem cells, posing concerns. Moreover, recent research has indicated that the mutation of normal stem cells within tissues may contribute to the emergence of cancer-initiating cells. The diverse array of secreted molecules from stem cells, encompassing growth factors and cytokines, is collectively termed the stem cell secretome. The application of the stem cell secretome for severe cutaneous wounds holds promise as a potential approach to address the limitations associated with the viable transplantation of replacement cells. The therapeutic efficacy of mesenchymal stem cells (MSCs) secretome in wound healing has been demonstrated. However, there remains a need for a more advanced biomaterial-based carrier system capable of holding a larger quantity of secretome and delivering them more efficiently to enhance wound regeneration. The secretome plays a crucial role in the wound- healing process by stimulating and coordinating key cells, including keratinocytes, fibroblasts, and endothelial cells. The current study explored the potential of the secretome derived from Rat dermal fibroblast cells incorporated in alginate – soy lecithin hydrogel to expedite the healing of cutaneous wounds both in vitro and in vivo. To aid the biocompatibility of the hydrogels, natural polymers such as alginate (Alg) were used. Alginate hydrogel dressing provides essential functions, including maintaining a moist environment, absorbing wound exudate, and facilitating swelling. Natural agents such as Soy lecithin (SL) which has good biocompatibility, were used to modify the internal structure of the hydrogel during the preparation process. Before incorporating the secretome, the alginate-soy lecithin hydrogel underwent evaluation for its physicochemical and physicomechanical attributes, exhibiting favourable structural characteristics. Subsequently, the harvested secretome underwent qualitative and quantitative analysis, focusing on factors like vascular endothelial growth factor (VEGF). Notably, after 72 hours, the secretome exhibited a heightened concentration of VEGF, reaching 2400 pg./ml, which holds a crucial role in angiogenesis. This study observed various properties, including fluid absorption (897.89% for secretome hydrogel (S. gel) and 4959.22% for Lyophilized secretome hydrogel (LS. gel) within 24 hours), degradation (43% for LS.gel and 94.57% for S.gel within 7 days), and mechanical characteristics (storage modulus of 2890 Pa and loss modulus of 773.4 Pa). Additionally, the in vitro bioactive release profile demonstrated an initial burst of protein release (56.6%) within 8 hours, leading to a total release of 60.5% within 3 days. After incorporating secretome into the alginate-soy lecithin hydrogel, it showed excellent biocompatibility with cell viability exceeding 100%. This resulted in promising performance, indicating non-toxic behavior (cell viability > 100%) when exposed to NIH 3T3 embryonic fibroblast cells and HacaT cells for 3 days. The developed hydrogel demonstrates the potential to accelerate wound closure in vitro by effectively stimulating cell migration and proliferation in fibroblasts and keratinocyte cells showing scratch closure (87.4%) within 72 hours on NIH 3T3 cells, while (72.3%) closure on HacaT cells. In vitro experiments were followed by in vivo assessments, which demonstrated that the secretome-loaded alginate-soy lecithin hydrogel functioned as a protective wound dressing, maintaining moisture and expediting wound healing. This acceleration was attributed to the sustained delivery of growth factors and cytokines from the secretome, enhancing cell-to-cell communication and promoting tissue remodeling. The hydrogel showed superior wound healing capabilities compared to a commercial product (Pharma-plast A) and a control group, with notable scar-less tissue regeneration after 21 days. These findings underscore the potential of fibroblast cell secretome hydrogel as an effective treatment for cutaneous wounds, improving the delivery of therapeutic biomolecules.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Hydrogel; Wound healing; Secretome; biomaterials; tissue regeneration; SDG-3: Good health and well-being